Electrochemical Deposition: Properties and Applications (MDPI - Multidisciplinary Digital Publishing Institute, 2024)
The Special Issue contains topical papers on the latest research, development, and application of electrochemical deposition method. The method is based on the chemical reduction of metal ions or their complexes. It is an almost universal way of making material coatings on the surface of conductive substrates by electrolysis of aqueous solutions containing metal ions or complexes. Electrochemical deposition is an inexpensive and relatively fast method that can be applied on an industrial scale for nano- and micro-structured coatings over a large area.With deep respect, we dedicate this Special Issue to the memory of the distinguished scientist Assoc. Prof. Dr. Konstantin Lovchinov (Bulgarian Academy of Sciences), who was its initiator and the main Guest Editor.